2015
DOI: 10.1387/revpsicodidact.12978
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Value Profiles and Analysis to Adolescent Behavior and Social Attitudes // Perfiles de valores interpersonales y análisis de conductas y actitudes sociales de adolescentes

Abstract: The aims of this study are to identify the interpersonal value profiles and analyze whether there are differences with respect to behavior and social attitude in a sample made up of 885 Compulsory Secondary Education (ESO) students (14-17 years), of whom 49.8% (n = 441) were males and 50.2% (n = 444) were females. The results show the identification of three different interpersonal value profiles corresponding to different levels of antisocial and criminal behavior. Thus the ARL-BCB (high recognition and leade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 30 publications
1
10
0
8
Order By: Relevance
“…Some researchers pointed out that interpersonal factors of IGD have been under-researched [4,11,12]. Interpersonal factors have been highlighted as a crucial role in understanding and addressing internal and external behavioral problems of adolescents [13,14]. This study focused on potentially important interpersonal correlates of adolescent IGD.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers pointed out that interpersonal factors of IGD have been under-researched [4,11,12]. Interpersonal factors have been highlighted as a crucial role in understanding and addressing internal and external behavioral problems of adolescents [13,14]. This study focused on potentially important interpersonal correlates of adolescent IGD.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, having these data is going to enable preventive programs to be designed for implementing, not only adequately, but also at the right time for them to be effective. From this approach, considering the variability of factors that intervene in both problems [29,[31][32][33][34][35][36], they should be included in future lines of research. Funding: This research received no external funding.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in combination with sensation-seeking behavior repertoires, it has been shown that both work as predictors of different types of aggression [27,28]. In addition to individual factors [29][30][31], adopting certain risk behaviors is also subject to other determinant factors in the construction of self-concept [32,33] and personal wellbeing [34], whether related to family members or peer group [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Del mismo modo, el consumo de drogas se ha relacionado con otras acciones de riesgo o antisociales (Cerezo, Méndez, & Ato, 2013;Gázquez, Pérez-Fuentes, Carrión, Luque, & Molero, 2015;Guillén, Roth, Alfaro, & Fernández, 2015;Pérez-Fuentes, Molero, & Gázquez, 2019).…”
Section: Introductionunclassified